Fecal microbiota transplantation (FMT) and live biotherapeutic products (LBPs): from standard treatment of Clostridioides difficile to emerging perspectives in neuropsychiatry - Czwałga, Piotr; Magiera, Michał; Koprowska, Patrycja; Sikora, Miłosz (Journal of Education, Health and Sport, 2026)
Background: Fecal Microbiota Transplantation (FMT) has evolved from an experimental procedure into a recognized standard in the treatment of intestinal dysbiosis. Although this method is widely associated with the therapy of C. difficile infections, a growing understanding of the microbiota-gut-brain axis suggests its potential in the treatment of neurodevelopmental and psychiatric disorders. Aim: The aim of this review is to discuss the efficacy of FMT in the standard treatment of C. difficile infections, as well as to evaluate its potential in managing neurodevelopmental disorders (ASD, ADHD) and depression. Material and methods: The analysis was based on a review of English-language literature from the years 2019–2025, along with selected historical references. The query was conducted in the PubMed, Google Scholar, and Web of Science databases using terms related to fecal microbiota transplantation, gut microbiota, donor screening, C. difficile infections and live biotherapeutic products. Results: Treatment efficacy is the result of the interaction between donor and recipient characteristics. In cases of recurrent C. difficile, FMT remains an important therapeutic alternative, currently complemented by standardized live biotherapeutic products (LBPs) such as Rebyota and Vowst, which eliminate the issue of sample variability. In psychiatry, distinct mechanisms of action are observed. In patients with ASD and ADHD, neurotransmitter modulation and inflammation reduction occur, whereas in depression, the efficacy of microbiotic interventions strictly depends on the integrity of the vagus nerve. Conclusions: The evolution of FMT toward ready-to-use pharmaceutical products confirms its efficacy in C. difficile infections, and growing evidence suggests its applicability in neuropsychiatric disorders. The future of the method depends on optimizing the donor-recipient-procedure triad and implementing precise bacterial consortia to minimize the risk of failure.